INTEGRATING THE SHADOWING TECHNIQUE WITH AN AI-POWERED MOBILE APPLICATION TO IMPROVE STUDENTS’ PRONUNCIATION AND SPEAKING FLUENCY - Sri Rahayu, Yayu; Dessy Maulida, Restu; Wintarsih, Wintarsih (Universitas Jambi, 2025)
This study investigates the effectiveness of integrating the shadowing technique with the AI-powered mobile application ELSA Speak to enhance pronunciation and speaking fluency among second-semester students of the English Language Education Study Program. A quasi-experimental design was employed, with a sample of 45 students divided into an experimental group and a control group. Data were collected through pre-tests, post-tests, and student questionnaires. Over six meetings, the experimental group utilized the shadowing technique alongside ELSA Speak, while the control group received traditional instruction. Results indicate that the experimental group showed significant improvement in both pronunciation and speaking fluency compared to the control group. This study concludes that integrating shadowing with AI-powered applications like ELSA Speak is an effective strategy for developing students’ oral English proficiency.